2022
DOI: 10.48129/kjs.10955
|View full text |Cite
|
Sign up to set email alerts
|

Association between CAST and MSTN gene polymorphisms with growth traits in Awassi sheep

Abstract: This study aims to identify the association between CAST/MspI and MSTN/HaeIII polymorphism with growth traits in Awassi sheep. A total of 129 (male and female) Awassi sheep were used in the study. Growth traits (Body weight BW, body length BL, chest depth CD, heart girth HG and withers height WH) were taken from animals at one year old. PCR-RFLP analysis was used to detect CAST polymorphism (Exon 1C/1D) and MSTN (Exon 3) genes. Three genotypes (MM, MN and NN) were observed for CAST/MspI polymorphism with allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In studies, the m gene is seen at higher frequencies compared to the M gene (Soofy et al, 2009;Jamshidi et al, 2014;Akbari et al, 2015;Dimitrova et al, 2016;Lazar et al, 2016;Bayraktar, 2020;Haren et al, 2020), which is consistent with allele gene frequencies in our study.…”
Section: Gene and Genotype Frequencies And Genetic Equilibrium Test R...supporting
confidence: 91%
See 1 more Smart Citation
“…In studies, the m gene is seen at higher frequencies compared to the M gene (Soofy et al, 2009;Jamshidi et al, 2014;Akbari et al, 2015;Dimitrova et al, 2016;Lazar et al, 2016;Bayraktar, 2020;Haren et al, 2020), which is consistent with allele gene frequencies in our study.…”
Section: Gene and Genotype Frequencies And Genetic Equilibrium Test R...supporting
confidence: 91%
“…Concerning different sheep breeds with regard to the MSTN gene, the Dalagh sheep breed (Azari et al, 2012), Zel sheep breed (Dehnavi et al, 2012), Karak- achan sheep breed (Bozhila-Sakova et al, 2016), and the Bulgarian Karnobat Merino sheep breed (Dimitrova et al, 2017) were found to be monomorphic. While the Mehreban sheep breed (Jamshidi et al, 2014), Kordi sheep breed (Akbari et al, 2015), Black-Headed Teleorman sheep breed (Lazar et al, 2016), Nilagiri sheep breed (Sahu et al, 2019), and Awassi sheep breed (Bayraktar, 2020) were found to be polymorphic with only two genotypes, the Sanjabi sheep breed (Soufy et al, 2009), Bulgarian Merino sheep breed (Dimitrova et al, 2016), and Batur sheep breed (Haren et al, 2020) were reported to be polymorphic with three genotypes. While studies indicating the MSTN gene polymorphism reported the mm genotype at a higher frequency than the MM genotype, the findings were consistent with our study.…”
Section: Gene and Genotype Frequencies And Genetic Equilibrium Test R...mentioning
confidence: 99%
“…In contrast, fattening increases size caused by increased fatty tissue (Bayraktar and Shoshin, 2022b;Jo et al, 2009). With the development of molecular techniques, it has become possible to identify genes that directly or indirectly affect the growth characteristics of animals (Bayraktar and Shoshin, 2022c;Park et al, 2018). Acyl coenzyme A, monoacylglycerol acyltransferase (MOGAT), also known as MGAT, is a vital enzyme that plays an active role in catalyzing the synthesis of triacylglycerol (TAG) and diacylglycerol (DAG; Lee and Kim, 2017;Cao et al, 2003;Hall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%